Studi Kandungan Logam Berat Pb, Cu, Cd, Cr Pada Kerang Simping (Amusium pleuronectes), Air Dan Sedimen Di Perairan Wedung, Demak Serta Analisis Maximum Tolerable Intake Pada Manusia - Azhar, Husnan; Widowati, Ita; Suprijanto, Jusup (977-2407769)
Wedung, Demak which have large potential of asian moon scallop (Amusium pleuronectes). This potential has leaded the increasing activities of fishing, industrial, and dense residential in Wedung. Those activities were thought to be one of the sources of heavy metals (Pb, Cu, Cd, Cr) accumulated in the simping. This study was aimed to determine the concentration of Pb, Cu, Cd, Cr in the A. pleuronectes, in the water and the sediment. Moreover, this study was also aimed to investigate the maximum weekly consumption A. pleuronectes which contained Pb, Cu, Cd, and Cr in Wedung waters area, Demak. The study was conducted in October-November 2011. The method used in this study was a study case method, while the purposive sampling method was used to determine the sampling locations. Sampling was conducted once every two week, with three repetitions. AAS (Atomic Absorbtion spectrophotometry), were used to analyze the heavy metal concentration, while the consumption of security analysis was used to analyze the MTI (Maximum Tolerable Intake). The range of the analysis results of Pb concentration in the scallop’s shells were 33,1362 – 35,0762 ppm, and 11,1272 – 13,0852 ppm in the sediments, while the concentration in the soft tissues and water, were not detected. The Cu concentration in the soft tissue were ranged from 8,9849 – 9,4659 ppm, where in the scallop’s shells were 11,9836 – 12,2358 ppm, water were 0,07 – 0,14 ppm, and in the sediments were 13,0624 – 17,6040 ppm. The Cd concentration in soft tissue were ranged from 5,9212 – 8,0136 ppm, scallop’s shell were 2,6195 – 5,0125 ppm, and water were 0,01 ppm at 2nd and 3rd samplings, while at the first sampling was not detected, whereas in the sediments the concentration ranged from 0,4694 – 0,7257 ppm. Cr concentration in the soft tissue were only detected in the third sampling with 0,7285 ppm, while in the scallop’s shells ranged from 1,9694 – 2,6924 ppm, and in the sediments were 0,9693 – 1,6933 ppm, while its concentration in water was not detected. Maximum weekly intake of scallop in Wedung water which are safe for consumption were 22,64 kg for Cu; 0,06 kg for Cd; and 5,76 kg of Cr per week for people with average body weight 60 kg, while the Pb concentration not detected.